Obraz rodziny polskiej w gimnazjalnych podręcznikach wychowanie do życia w rodzinie w latach 1999-2007 - Szybalska, Mariola (Karkonoska Państwowa Szkoła Wyższa, 2011)
The analysis of structure and content of the Family Life Education manuals aims at making the readers familiar with the concept of a contemporary Polish family which was presented in the curriculum content of the subject Family Life Education from 1998-2007.
Keywords: textbooks; Education for Family Life; family; health; dysfunctional families; family relations; objectives of the family